Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ ÑÐ°Ñ…Ð°Ñ€Ð¾Ð² Ð½Ð° Ð´ÐµÐ³Ð¸Ð´Ñ€Ð°Ñ‚Ð°Ñ†Ð¸ÑŽ Ð±Ð¸Ð¾Ð¿Ð¾Ð»Ð¸Ð¼ÐµÑ€Ð½Ñ‹Ñ… Ð¼Ð¾Ð»ÐµÐºÑƒÐ» Ð² Ð¿Ñ€Ð¾Ñ†ÐµÑÑÐµ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ñ - Rugal, A. A.; Barvinchenko, V. N.; Galagan, N. P.; Siora, I. V.; Turov, V. V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2007)
Protein molecules’ hydration in the presence of sugars: glucose, fructose and sucrose were studied by NMR-spectroscopy. The parameters of hydration, concentration of bound water and value of interfacial energy were determined over a wide range of component concentrations. It was shown with exemplifying using the serum albumin, that low-molecular compounds (sugars) could replace an intraglobular water. The maximal effect of dehydration was observed for sucrose. In this case protein molecules change their property and capability to be adsorbed on a surface of fine-grained silica, which is reduced by 25% as a result of the forming complexes.